STRATEGI PENERAPAN BMT UGT SIDOGIRI CABANG PEMBANTU SONGGON TERHADAP PEREKONOMIAN MASYARAKAT DESA SONGGON KECAMATAN SONGGON KABUPATEN BANYUWANGI - Edy Imam Supeno; Noval mohamad Rofik (NATUJA: Jurnal Ekonomi Syariah, 2022)
The development of the shari'ah financial industry has informally begun before the issuance of a formal legal framework as the operational foundation of Islamic banking in Indonesia. This research uses normative approach methods which means in discussing this research problem using materials related to the title of the study, both written and unwritten. The data and data sources required in this study are primary data and secondary data. Material analysis uses descriptive analysis. The results showed that the creation of various financial services that became the needs of society in general. Such as deposit products, loans, online payment services, and so on. The products used are also based on the Quran and The Hadith which certainly provides enormous benefits for the lives of all people. Because, in the use of the products offered, there is no interest (usury) to take advantage of customers. All that is used is the revenue sharing (mudharabah) between customers and BMT self-sufficient.